EVALUASI KEMUDAHAN TRANSFER MARKA SSR PADI UNTUK MENGANALISIS KERAGAMAN GENETIK FAMILI POACEAE TOLERAN KEKERINGAN - Fatimah, Fatimah; Masumah, Masumah; Prasetiyono, Joko; Sustiprijatno, Sustiprijatno (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACTAnticipating climate change and its impacts on crop production, it requires the development of adaptive rice varieties that respond to drought stress and minimize the damage while keeps growing and maintaining yield. The aim of this study was to evaluate the transferability of rice simple sequence repeat (SSR) markers to Poaceae family and analyze the genetic diversity among 16 accessions of Poaceae family (12 genera and 14 species) using 41 rice SSR markers. The result revealed that the transferability of rice SSR markers was varied. High amplification produced in rice group (>70%) and low amplification in grass group (<30%) with an average of 35.2%. A total of 128 cross-species alleles were identified with an average of 3 alleles/locus. The value of gene diversity ranged from 0.15 to 0.83 with an average of 0.53 and the value of Polymorphic Information Content (PIC) ranged from 0.14 to 0.80 with an average of 0.46. The results of phylogenetic analysis determined two clusters at similarity coefficient of 0.72. The first cluster consisted of 14 accessions from Poaceae family (12 genera and 14 species) while the second cluster consisted of two cultivated rice varieties (Inpari 30 and Situ Bagendit). The genetic relatedness data revealed from this study could be used as basic information for parental selection. The 14 accessions of Poaceae family have a potential for drought tolerant donor and separated clearly from cultivated rice varieties (Inpari 30 and Situ Bagendit) for recipient parents in spike-stalk injection method (SIM) to develop drought tolerant rice varieties.  Keywords: Cross amplification, Drought tolerant, Inpari 30, Situ Bagendit